Protective effect of quercetin on kidney diseases: From chemistry to herbal medicines - Chen, Yi-Qin; Chen, Hao-Yin; Tang, Qin-Qi; Li, Yi-Fan; Liu, Xu-Sheng; Lu, Fu-Hua; Gu, Yue-Yu (Frontiers in Pharmacology, 2022)
Kidney injuries may trigger renal fibrosis and lead to chronic kidney disease (CKD), but effective therapeutic strategies are still limited. Quercetin is a natural flavonoid widely distributed in herbal medicines. A large number of studies have demonstrated that quercetin may protect kidneys by alleviating renal toxicity, apoptosis, fibrosis and inflammation in a variety of kidney diseases. Therefore, quercetin could be one of the promising drugs in the treatment of renal disorders. In the present study, we review the latest progress and highlight the beneficial role of quercetin in kidney diseases and its underlying mechanisms. The pharmacokinetics and bioavailability of quercetin and its proportion in herbal medicine will also be discussed.